2015
DOI: 10.1039/c5ra04395f
|View full text |Cite
|
Sign up to set email alerts
|

Quantum molecular modelling of ibuprofen bound to human serum albumin

Abstract: The binding of the nonsteroidal anti-inflammatory drug ibuprofen (IBU) to human serum albumin (HSA) is investigated using density functional theory (DFT) calculations within a fragmentation strategy.Crystallographic data for the IBU-HSA supramolecular complex shows that the ligand is confined to a large cavity at the subdomain IIIA and at the interface between the subdomains IIA and IIB, whose binding sites are FA3/FA4 and FA6, respectively. The interaction energy between the IBU molecule and each amino acid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 63 publications
(161 reference statements)
3
26
0
Order By: Relevance
“…It has been seen that very few molecular studies in the literature have reported on MD-based molecular modelling to describe solid dispersion process as well as drug-polymer interactions. [7][8][9][10][11][12][13][14][15][16] Recently, the quantum mechanical (QM) calculations (Gaussian 09) were used to identify drug/polymer interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been seen that very few molecular studies in the literature have reported on MD-based molecular modelling to describe solid dispersion process as well as drug-polymer interactions. [7][8][9][10][11][12][13][14][15][16] Recently, the quantum mechanical (QM) calculations (Gaussian 09) were used to identify drug/polymer interactions.…”
Section: Introductionmentioning
confidence: 99%
“…According to information in the literature, DCF binds to Site I with high affinity and Site II with low affinity [40,41]. IBU binds mainly to Site II with high affinity, but some articles also describe its binding to a fatty acid binding site located at the interface between the IIA and IIB domains [42,43]. Several articles describe the binding of CP to Site I [38,44], but in a study by Tao et al a secondary binding site in subdomain IIIA (Site II) was also observed [45].…”
Section: L-tryptophanmentioning
confidence: 99%
“… 50 and Dantas et al . 51 to calculate binding affinity in protein-ligand complexes, by assuming different values of the dielectric constant ( ε ) to take into account the effect of the protein and solvent environment in the evaluation of the electrostatic energies. Here, we have employed the MFCC approach together with the CPCM (Conductor-like Polarizable Continuum Model) continuum solvation model 52 with dielectric constants ε considered to be 20 ( ε 20 and 40 ( ε 40 ), respectively) to increase the similarity with the protein environment and estimate energy effects, such as the electrostatic polarization promoted by the solvent.…”
Section: Methodsmentioning
confidence: 99%